Pohřební zvyklosti mladé církve: Prolegomena k nekrogeografii Církve československé husitské (a pravoslavné církve) v meziválečném období - Nešpor, Zdeněk R. (Lidé města, 2015)
This study complements and concludes the necrogeographic analysis of the Czech lands, and presents an overview of the confessional burial grounds of the Czechoslovak (Hussite) Church and the Orthodox Church. We can glean from the available sources that local and regional “Czechoslovak” cemeteries were established, although the Church as a whole (unsuccessfully) attempted to “nationalise” existing cemeteries. Later, the Church came to accept the interconfesional character of these cemeteries, and at the same time, it vehemently established its own columbariums and urn burial grounds. Despite of the fact that the Czechoslovak (Hussite) Church permitted the cremation of some members of other churches, as well as of atheists, and for some time, its clergymen took part of the cremation ceremonies, the Church itself did not discuss the matter, nor did it form any official Church standpoint on this issue. Due to internal Church reasons, cremation as such was only inadvertently proclaimed on the pages of its central ideological magazine, Český zápas, and that beginning from the mid-1920s, although cremation was de facto already the standard within the Church at this time. The burial practices of the members of the Czechoslovak (Hussite) Church in the interwar period thus anticipated the future inclinations of the majority of Czech society.